The middle as a voice category in Bantu: Setting the stage for further research - Dom, Sebastian; Kulikov, Leonid; Bostoen, Koen (Lingua Posnaniensis, 2016)
The main goal of our paper is to give a first, general description of middle voice in Bantu. As will be shown, this language group has a set of verbal derivational morphemes that challenges some of the concepts related to the middle domain. First of all, as of yet no description has been found of a language having more than one middle marker, yet many Bantu languages have up to four or five derivational morphemes that cover several parts of the semantic domain of the middle. Secondly, provided that the polysemy patterns of these morphemes only partially cover what is generally considered the “canonical” middle domain, we will call these “quasi-middle” markers. The fact that these verbal morphemes also convey notions that are usually not considered to belong to the domain of the canonical middle calls for a reassessment of what constitutes the semantic core of this voice category cross-linguistically. Although the theoretical implications of these new data are not the central focus of our paper, the basic description that we aim to provide of the middle in Bantu can nevertheless contribute to further discussion on this intricate voice category.